Skin diseases in patients with primary psychiatric conditions: A hospital based study - Nayera H. Moftah; Abeer M. Kamel; Hussein M. Attia; Mona Z. El-Baz; Hala M. Abd El-Moty (Springer, 2019)
Background: Although the relationship between skin diseases in patients with primary psychiatric conditions is important for patient management, studies on this issue are limited. Objective: To detect the frequency and type of cutaneous disorders among patients with primary psychiatric conditions. Subjects and methods: This analytic cross-sectional study was conducted on a total of 400 subjects - 200 patients with primary psychiatric disorders and 200 age and sex matched individuals free from primary psychiatric disorders. Patients included in the study were diagnosed according to The Diagnostic and Statistical Manual of Mental Disorders (DMS IV) Criteria. A specially designed questionnaire including socio-demographic data, medical history, family history and dermatological examination was applied. The data were statistically analyzed. Results: There was a significant statistical increase in the prevalence of skin diseases in general and infectious skin diseases in particular in psychiatric patients compared with non-psychiatric patients (71.5% versus 22%, P < 0.001) and (48% versus 11%, P < 0.001), respectively. Parasitic infestations (42.7%) were the most common infectious skin diseases in psychiatric patients (P < 0.001). Infectious skin diseases in psychiatric patients were seen most in patients diagnosed with schizophrenia (83.6%) and least in obsessive compulsive disorders (30%)(P < 0.001). Psychogenic skin disorders were found in 8.4% of psychiatric patients with skin diseases; delusional parasitosis was the most common (50%). Conclusion: Health education of psychiatric patients and/or of their caregiver and periodic monthly inspection of psychiatric patients are highly indicated for the prevention and control of infectious skin diseases in primary psychiatric patients.